(untitled) (Herald of the National Children’s Medical Center, 2025)
In pediatric anesthesiology, assessing the depth of sedation is a critically important task to ensure adequate anesthesia and prevent intraoperative awareness or excessive suppression of consciousness. Bispectral index (BIS) monitoring, based on EEG analysis, enables objective control of the anesthesia level. The use of BIS is especially relevant when using sevoflurane, which has a favorable safety profile in pediatric practice.